Thyroid hormone levels and BMI-SDS changes in adolescents with obesity - Staníková, Daniela; Krajčovičová, Lea; Lobotková, Denisa; Vitariušová, Eva; Tichá, Ľubica; Pribilincová, Zuzana; Ukropcová, Barbara; Ukropec, Jozef; Staník, Juraj (Frontiers in Endocrinology, 2023)
Background. Thyroid hormones play an important role in energy metabolism and weight control, explained mostly by inducing thermogenesis and increasing basal metabolic rate. It has recently been shown that FT4 levels are associated with food preferences, which might also play a role in modulating body weight. The aim of this longitudinal follow-up study was to analyze the relationship of thyroid hormones levels (FT4, TSH) at baseline with weight/BMI-SDS changes in children and adolescents with obesity.Methods. Three hundred seventy-seven children and adolescents have been enrolled to this study and followed up without a systematic intervention program for 5.59±1.85months.Children and adolescents were divided into three subgroups: 1) 144 adolescents with obesity (15-19 years), 2) 213 children with obesity (10-14.9 years), and 3) 20 lean adolescents (15-19 years). Thyroid hormones were measured at the baseline, and anthropometry was performed at the baseline and during the follow-up. For further analyses, participants were divided according to the BMI-SDS change into two groups: 1. with BMI-SDS decrease, and 2. with BMI-SDS increase.Results. Adolescents with obesity from the BMI-SDS decrease group had significantly lower baseline serum levels of TSH compared to the BMI-SDS increase group (2.4±1.0 vs. 3.2±2.0mIU/l; p=0.005). Similar difference was found for FT4 levels (14.7±2.2 in the BMI-SDS decrease group vs. 15.5±2.7pmol/l in the BMI-SDS increase group, p=0.048). Moreover, the BMI-SDS decrease was present in significantly higher percentage of adolescents with obesity with lower than median TSH level compared to those with higher than median TSH level at baseline (61.1% vs 38.6%, p=0.011). Likewise, the BMI-SDS decrease was present in significantly higher percentage of adolescent females with obesity and lower than median FT4 compared to those with higher than median FT4 level at baseline (70.6% vs. 23.5%, p˂0.001).No associations of baseline thyroid hormones with the BMI-SDS change were observed in children with obesity or lean adolescents.Adolescents with obesity and increased BMI-SDS during the follow-up had significantly higher baseline levels of both TSH and FT4 compared to BMI-SDS decrease group. These results support the previous findings that higher FT4 in individuals with obesity may influence weight gain.